The Contributions of Biomedical Informatics to the Fight Against Bioterrorism - Kohane, Isaac S. (American Medical Informatics Association, 2002)
A comprehensive and timely response to current and future bioterrorist attacks requires a data acquisition, threat detection, and response infrastructure with unprecedented scope in time and space. Fortunately, biomedical informaticians have developed and implemented architectures, methodologies, and tools at the local and the regional levels that can be immediately pressed into service for the protection of our populations from these attacks. These unique contributions of the discipline of biomedical informatics are reviewed here.